DIGITAL FLIPBOOK-BASED LEARNING MEDIA DESIGN IN INTEGRATED THEMATIC LEARNING ON THE THEME OF GROWTH AND DEVELOPMENT OF LIVING THINGS IN CLASS III INCLUSIVE ELEMENTARY SCHOOL - Zen, Ahmad Muzakki; Muhith, Abd; Wahono, Suparwoto Sapto (ATTA`DIB, 2024)
This study aims to overcome the difficulty of understanding class III Inclusive students at Al-Irsyad Al-Islamiyah Jember Elementary School in thematic learning on the theme of growth and development of living things. Data from 25 students showed that 80% had difficulty with conventional methods, while 90% needed innovation, especially digital flipbook-based me-dia. As many as 85% of students like digital media, and 83% are interested in interesting il-lustrations. More than 90% agreed with the development of Digital Flipbooks as learning media. This study used the ADDIE research and development method, with validation in-struments and student response questionnaires. Data analysis involved expert judgment, per-centage of questionnaire results, and one-group pretest posttest design. The results of the study are expected to contribute to improving the understanding of grade III Inclusive stu-dents on the theme of growth and development of living things through digital flipbook-based learning media.